Assessment of learning needs of nursing staff working in kidney transplantation units at a University hospital = (3Jbjje GdEMJjGLGJ GdeYQajI dCYVGA gjFI GdJeQjV GdYGedjf HhMOGJ RQY Gdcdi HEMOi GdeSJTajGJ GdLGeYjI (B/ s - Farida Abouelfotouh Abouhiba; Fatma Ahmed Abed; Hanaa Youssry Hashem (Cairo : Farida Abouelfotouh Abouhiba, 2015)
The knowledge of healthcare workers towards kidney transplantation (KT) are fundamental in the development and sustainability of transplant programs. Healthcare workers can influence the willingness to improve their competences and nursing care of kidney transplantation recipients. The aim of this study was to assess learning needs of the nursing staff working in kidney transplantation units at a university hospital. The following research question was formulated: What are the learning needs of nursing staff working in kidney transplantation unit at a university hospital? An exploratory descriptive research design was adopted to fulfill the aim of the study. A sample of convenience included (sixty nurses) working in the kidney transplantation unit at New Kasser El-ainy teaching hospital which affiliated to Cairo University. Two tools were designed and utilized to collect data pertinent to the study: (a) Back ground data sheet which contained sociodemographic and work related data. (b) Learning needs assessment questionnaire which included questions that assess nurse{u2019}s knowledge regarding pre, during, and post operative care for patient undergoing kidney transplantation. The study findings revealed that the studied subjects had unsatisfactory level of knowledge about kidney transplantation (basic, preparatory care before KT., and preparatory care for discharge). On the other hand they had satisfactory level of knowledge about care during the operation of KT. and post transplantation care. Conducting an in-service training program for nurses who works at the kidney transplantation unit is recommended
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Nursing Services Administration
Issued also as CD
Keywords: kidney transplantation; kidney transplantation staff nurses; Learning needs assessment